Translation and validation of Inflammatory Bowel Disease Quality of Life Questionnaire (IBDQOL) into Bengali - Hussain, Muhammad Belal; Aftab, Hafeza (Bangladesh Journal of Medicine, 2024)
Background: Inflammatory bowel disease (IBD) is a chronic bowel disorder with high morbidity impairing quality of life of the patient. The IBD Questionnaire (IBDQ) is available to measure health-related quality of life (HRQO) in IBD patients. The IBDQ has been validated in many countries, there is no Bengali version till today. The aim of this study was to translate and validate the UK English version of IBDQ into Bengali. Methods: The UK version IBDQ was translated into Bengali considering local socio-cultural context according to Beaton et al., 2000. Content validity, construct validity, internal consistency and test-retest reliability were analyzed separately. Content validity was assessed by the item-level & scale level content validity indices (I-CVI & S-CVI) and modified kappa (k*) agreement. Construct validity was assessed by correlations of IBDQ with SF-36 by Pearson’s correlation coefficients. Cronbach’s alpha values were used to assess internal consistency. Intra-class correlation coefficient was used to assess test–retest reliability. The Bengali translated questionnaire was tested upon 64 IBD patients. Results: The Bengali version of the IBDQ shown well understandability. I-CVI, S-CVI, and modified kappa (k*) were found 0.75-1, 0.91,0.67-1 respectively. There was high positive correlation between the Bengali IBDQ domains and the SF-36 dimensions(r=Ã0.70). It also showed excellent internal consistency (Crohnbach’s alpha=0.91) and high reliability (intraclass correlation coefficient 0.940–0.998). Conclusion: The translated Bengali IBDQ was found a valid and reliable instrument for assessing HRQOL in Bengali speaking IBD patients. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation:163